Apical and periapical repair of dogs' teeth with periapical lesions after endodontic treatment with different root canal sealers. - Leonardo, Mário Roberto; Salgado, Antônio Alberto; da Silva, Léa Assed; Tanomaru Filho, Mário (FapUNIFESP (SciELO), 2003)
The aim of this study was to evaluate the apical and periapical repair after root canal treatment of dogs' teeth with pulp necrosis and chronic periapical lesion using different root canal sealers. After periapical lesion induction, forty-four root canals of 3 dogs were submitted to biomechanical preparation using 5.25% sodium hypochlorite as an irrigating solution. A calcium hydroxide dressing (Calen PMCC) was applied for 15 days and the root canals were filled using the lateral condensation technique with gutta-percha points and Sealapex, AH Plus or Sealer Plus for sealing. After 180 days, the animals were sacrificed by anesthetic overdose and the obtained histological sections were stained with hematoxylin-eosin for optical microscopic analysis of the apical and periapical repair. The groups filled with Sealapex and AH Plus had better histological repair (p < 0.05) than the group filled with Sealer Plus, that had unsatisfactory results.
Keywords: biomaterial; biomedical and dental materials; calcium hydroxide; epoxy resin; root canal filling material; animal; comparative study; dog; drug combination; drug effect; endodontics; evaluation; female; male; periodontium; standard; tooth periapical disease; tooth pulp; wound healing; Animals; Biocompatible Materials; Calcium Hydroxide; Dental Pulp Cavity; Dogs; Drug Combinations; Epoxy Resins; Female; Male; Periapical Abscess; Periapical Periodontitis; Periapical Tissue; Root Canal Filling Materials; Root Canal Irrigants; Root Canal Obturation; Wound Healing